Asaia Activates Immune Genes in Mosquito Eliciting an Anti-Plasmodium Response: Implications in Malaria Control - Cappelli, Alessia; Damiani, Claudia; Mancini, Maria Vittoria; Valzano, Matteo; Rossi, Paolo; Serrao, Aurelio; Ricci, Irene; Favia, Guido (Frontiers in Genetics, 2019)
In mosquitoes, the discovery of the numerous interactions between components of the microbiota and the host immune response opens up the attractive possibility of the development of novel control strategies against mosquito borne diseases. We have focused our attention to Asaia, a symbiont of several mosquito vectors who has been proposed as one of the most potential tool for paratransgenic applications; although being extensively characterized, its interactions with the mosquito immune system has never been investigated. Here we report a study aimed at describing the interactions between Asaia and the immune system of two vectors of malaria, Anopheles stephensi and An. gambiae. The introduction of Asaia isolates induced the activation of the basal level of mosquito immunity and lower the development of malaria parasite in An. stephensi. These findings confirm and expand the potential of Asaia in mosquito borne diseases control, not only through paratransgenesis, but also as a natural effector for mosquito immune priming.